If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13-3(x+2)=5x-9+2(x-7)
We simplify the equation to the form, which is simple to understand
13-3(x+2)=5x-9+2(x-7)
Reorder the terms in parentheses
13+(-3x-6)=5x-9+2*(x-7)
Remove unnecessary parentheses
+13-3x-6=+5x-9+2+*(+x-7+)
Reorder the terms in parentheses
13-3x-6=5x-9+(+2x-14)
Remove unnecessary parentheses
+13-3x-6=+5x-9+2x-14
We move all terms containing x to the left and all other terms to the right.
-3x-5x-2x=-9-14-13+6
We simplify left and right side of the equation.
-10x=-30
We divide both sides of the equation by -10 to get x.
x=3
| -33-6x=51-12x | | 38+4y-9=13y-13-3 | | -4(3+-9)=8(-8-t) | | 128+47= | | 13=21-4a | | 6x+42=2x+18 | | 6c-8ft=14ft | | 6x+41=2x+18 | | -1x+7=1x-17 | | -2y-y-11=1 | | 13=5+3b-14 | | 9x-12=3x-5 | | 1605+855= | | 1-8x=0 | | 5sqrtx+6=19 | | 42-18=3(x-9) | | 5a-10a-11=4 | | 41=36 | | -2x+10=18-4x | | 3(a-1)= | | (20x^3+17x^2+18x+16)= | | 10+8y=-40 | | 6n+4-8+32m=74 | | p=ipv | | (20x^3+17x+18x+16)= | | m-39=8 | | 2(3x-4)=x+7 | | 10+6x=7x+7 | | 7x-7=8x+3 | | r^2-6r=7 | | 2r=1.5(r+15) | | 7(6-6x)+11=-31 |